Learning Through Reflection: A Team’s Reflection on a Digital, Text-based Positive Health Coaching Intervention for Healthcare Professionals - Croia Loughnane; Róisín O’Donovan; Ashley P. Duggan; Pádraic Dunne (International Journal of Evidence Based Coaching and Mentoring)
Digital coaching has accelerated in recent years, expanding to encompass self-administered, coach-led, and automated coaching through video, email, and text. This article explores a coach’s reflections during a recent Randomised Controlled Trial (RCT) that examined the feasibility of text-based digital coaching for healthcare workers. In that study, twenty-three participants were randomised into a wait-list control (n=12) or intervention group (n=11) engaged in a 12-week text-based coaching intervention. The coach’s reflective journal, analysed via Reflexive Thematic Analysis (RTA) shows the potential scalability of text-based coaching, in addition to connection and significant rapport building despite nonverbal cues. However, technology instability and tech literacy can hinder digital coaching.